Expanding the phenotype associated with biallelic WDR60 mutations: Siblings with retinal degeneration and polydactyly lacking other features of short rib thoracic dystrophies. Issue 2 (22nd December 2017) - Kakar, Naseebullah; Horn, Denise; Decker, Eva; Sowada, Nadine; Kubisch, Christian; Ahmad, Jamil; Borck, Guntram; Bergmann, Carsten
Abstract : Ciliopathies are disorders of the primary cilium that can affect almost all organs and that are characterized by pleiotropy and extensive intra‐ and interfamilial phenotypic variability. Accordingly, mutations in the same gene can cause different ciliopathy phenotypes of varying severity. WDR60 encodes a protein thought to play a role in the primary cilium's intraflagellar transport machinery. Mutations in this gene are a rare cause of Jeune asphyxiating thoracic dystrophy (JATD) and short‐rib polydactyly syndrome (SRPS). Here we report on a milder and distinct phenotype in a consanguineous Pakistani pedigree with two adolescent sisters affected by retinal degeneration and postaxial polydactyly, but lack of any further skeletal or chondrodysplasia features. By targeted high‐throughput sequencing of genes known or suspected to be involved in ciliogenesis, we detected a novel homozygous N‐terminal truncating WDR60 mutation (c.44delC/p.Ala15Glufs*90) that co‐segregated with the disease in the family. Our finding broadens the spectrum of WDR60 ‐related phenotypes and shows the utility of broad multigene panels during the genetic work‐up of patients with ciliopathies.